2016
DOI: 10.1001/jamaoto.2016.0657
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality Metrics for Surgically Treated Laryngeal Squamous Cell Carcinoma

Abstract: IMPORTANCE Quality metrics for patients with laryngeal squamous cell carcinoma (SCC) exist, but whether compliance with these metrics correlates with improved survival is unknown. OBJECTIVE To examine whether compliance with proposed quality metrics is associated with improved survival in patients with laryngeal SCC treated with surgery with or without adjuvant therapy. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study included patients from a tertiary care academic medical center who had p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 20 publications
2
43
3
Order By: Relevance
“…Despite the NCCN’s endorsement of the preferred time to initiation of PORT for patients with HNSCC, the evidence underlying the recommendation is conflicted with regards to its effect on locoregional recurrence and survival 13 , with some finding benefit 1421 and others finding no influence 10,11,2226 . Many of these studies have been limited by retrospective single institution study design and small patient numbers 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the NCCN’s endorsement of the preferred time to initiation of PORT for patients with HNSCC, the evidence underlying the recommendation is conflicted with regards to its effect on locoregional recurrence and survival 13 , with some finding benefit 1421 and others finding no influence 10,11,2226 . Many of these studies have been limited by retrospective single institution study design and small patient numbers 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown inconsistent effects on locoregional recurrence and survival, with some finding benefit 1421 and others no influence 10,11,2226 . Most of the studies finding benefit to earlier initiation of adjuvant therapy were conducted over 15 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Graboyes et al reported data from surgically treated larynx cancer patients at a single, tertiary care high‐volume institution and did not find an association between survival and compliance with NCCN guidelines. NCCN treatment guidelines used were limited to referral for adjuvant radiation and chemotherapy, start of adjuvant therapy within 6 weeks, and surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies between guideline-directed care and delivered care have been described across the spectrum of pretreatment evaluation, treatment, and posttreatment surveillance for patients with oral cavity cancer 13 and laryngeal cancer 14,15 and in the receipt of adjuvant therapy for patients who have head and neck cancer with high-risk features. Discrepancies between guideline-directed care and delivered care have been described across the spectrum of pretreatment evaluation, treatment, and posttreatment surveillance for patients with oral cavity cancer 13 and laryngeal cancer 14,15 and in the receipt of adjuvant therapy for patients who have head and neck cancer with high-risk features.…”
Section: Frequency Of Care That Does Not Adhere To Nccn Guidelinesmentioning
confidence: 99%